Use the Power Rule of Exponents to simplify (10^3)^6

.(1 point)

3 answers

To simplify \((10^3)^6\) using the Power Rule of Exponents, you can apply the rule that states \((a^m)^n = a^{m \cdot n}\).

In this case, you have:

\[ (10^3)^6 = 10^{3 \cdot 6} \]

Now calculate \(3 \cdot 6\):

\[ 3 \cdot 6 = 18 \]

So, it simplifies to:

\[ 10^{18} \]

Therefore, \((10^3)^6 = 10^{18}\).

simplify

The expression \((10^3)^6\) simplifies to \(10^{18}\).

If you're looking for a numerical simplification, we can compute \(10^{18}\) as follows:

\[ 10^{18} = 1000000000000000000 \]

So the simplified result is:

\[ 10^{18} \text{ or } 1000000000000000000 \]